Proposta de modelo de apoio à decisão aplicado à conservação de bacias hidrográficas no nordeste brasileiro - Pinheiro, Laldiane de Souza (2023)
Changes in land use and land cover, such as deforestation, throughout the entire watershed promote a series of impacts on environmental services. Checking compliance with legislation regarding forest conservation, characterizizing the evolution of these changes over time, and having models that prioritize areas for protection action plans, are important for water resource management. From this perspective, this study aimed to propose a water resource management support model for management and conservation actions related to water supply and quality in watersheds, using multicriteria analysis.The study área included three microbasins belonging to distinct geo-environmental units:mountain, hinterland, and coast áreas in the Choró-Ce River Basin. Analyzing the evolution of land use and cover from 2012 to 2022, it was identified that there was a decrease in forest areas and an increase in anthropized áreas in all microbasins. Permanent preservation areas showed a percentage of conflict in their uses of 31%, 12% and 20% for the mountain, hinterland and coast basins, respectively. Strategic and priority conservation areas in the watershed were mapped with the proposed multicriteria model, using the Analytic Hierarchy Process (AHP) method to weigh the criteria. After consultation with experts, the criteria weights were defined as fallows: land use and land cover (0 .43), proximity to springs (0.23), proximity to drainage (0.13), proximity to aquifer recharge sources (0.12) and slope (0.09). This allowed for the identification of areas with very high, high, medium, and low priorities. Areas with very high priority are located in water producing regions. The Global Moran’s Index for the basins (0.413, 0.592 and 0.601) indicated spatial autocorrelation and that priority areas for conservation tend to cluster spatially, providing important information for decision making. Poor forest management in the microbasins is increasing environmental impacts and decreasing the environmental services they provide, such as the increase in local surface temperature and carbon emissions into the atmosphere. The analyzes presented emphasize the urgent need for tools that assist in efficient management, promoting recovery and conservation actions for watersheds.